Diagnóstico de salud bucodental y factores de riesgo en los estudiantes de décimo año de educación básica a tercero de bachillerato, en la unidad educativa Manuel José Rodríguez de la parroquia rural Malacatos, del cantón Loja; año 2013. - Palacios Arrobo, Tania Marina (2013)
Oral diseases, including dental caries, periodontal disease and malocclusion because of their frequency, local discomfort and aesthetic impact on the overall health cause, justifying their attention as a public health problem. Given this, we conducted a study of quantitative, descriptive and transversal, whose aim was to make the diagnosis of oral health and risk factors in the Education Unit Manuel José Rodríguez, of the parish of the canton Malacatos Loja 2013, examined 241 students, collecting information through dental and medical history survey. The results were : 84.6 % dental caries , gingival inflammation 32.7 % malocclusion in permanent dentition class III was 55.3%, the risk factors were not brushing 76.3 % , visit the dentist once a year for 42.7 % of consumption of cariogenic food once a day to 45.6 %. The prevalence of certain diseases indicates that the study population pays little attention to oral health care, adhering to ignorance of how to maintain it. Keywords: caries risk factors, gingival inflammation malocclusion